Mitos Weton pada Pernikahan Masyarakat Desa Gedangan Lamongan: Kajian Mircea Eliade - Apria Ningrum, Velida; Nabila Fajriyanti Muhyin; Agoes Moh Moefad (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
The myth remains a frequently encountered phenomenon in society, particularly among the Javanese people known for their spiritual sharpness. This article explains the myth of calculating "weton" in marriage ceremonies conducted by the community of Gedangan Village, Lamongan Regency. The article argues that the myth of calculating "weton" in marriage is not merely a superficial myth without any meaning or significance. Using a descriptive method, this article describes that the calculation of "weton" in marriage is the result of the interaction between ancestors and deities or other mystical entities, which, when viewed from Mircea Eliade's perspective, is commonly referred to as the sacred. This sacred element then manifests itself as symbols and myths in the form of the Javanese calendar system, which is later used as a reference for calculating "weton."